A spatiotemporal classification approach to evaluate the impacts of land use and land cover changes before and after the Três Irmãos reservoir formation in the Tietê River, Brazil - Lucchetta, Beatriz Cirino [UNESP]; Watanabe, Fernanda Sayuri Yoshino [UNESP]; do Carmo, Nariane Marselhe Ribeiro Bernardo (Springer Nature, 2023)
Land use and land cover (LULC) maps are relevant tools to recognize deep changes in the natural landscape and direct strategies to minimize environmental impacts, being an important apparatus to obtain useful information in making decision by managers from watershed committees, political leaders and environmental agencies. Using Landsat multispectral images, this study aimed to investigate the changes in LULC of a watershed, influenced by the construction of the dam of the Três Irmãos hydroelectric plant, located in the low course of the Tietê River. The images were acquired in 1990, 2000, 2010 and 2018, which covers the periods before and after the flood caused by the dam build. For each date, LULC maps were generated using the supervised classification Maximum Likelihood (ML) algorithm. Those analysis has allowed identify possible influences of the reservoir formation over LULC in the watershed. A deep analysis showed a significant change of natural vegetation were flooded due to the damming, being partially recovered, in percentage terms, over time around the new watercourse. This study presents a reduction of 67% in the natural vegetation area from 1990 to 2000, while there was an increase of 35,36% between 2000 and 2018, when compared to the area occupied by natural vegetation existing in 1990. In addition, areas of natural vegetation also have been replaced by cultivated areas, which are predominant in the watershed.
Keywords: Change detection; Environmental monitoring; Image classification; Land use and land cover; Watershed